2013
DOI: 10.1016/j.seizure.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of uncontrolled epilepsy in the Al-Kharga District, New Valley, Egypt

Abstract: A total of 437 patients with epilepsy were identified, 30.7% of whom (n=134/437) were uncontrolled, with a prevalence of 2.1/1000. A total of 52.2% of uncontrolled patients (n=70/134) were inappropriately treated, while 47.8% (n=64/134) were compliant with appropriate treatments. Video monitoring EEG of compliant uncontrolled patients demonstrated that 78.1% patients (n=50/64) had definite epilepsy, while 21.9% (n=14/64) had psychogenic non-epileptic seizures (PNES). A logistic regression analysis revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
7
23
1
Order By: Relevance
“…Our results agree with previous reports indicating that head injuries [14] are the most common underlying etiological cause of chronic epilepsy, with males being at a greater exposure risk. When comparing our results with another Egyptian study, led by Farghaly and his colleagues [35], they found that cerebrovascular stroke, rather than trauma, was the most common cause of symptomatic epilepsy among adults and the elderly while perinatal insults were the most common among children (< 18 years). This difference regarding adult epileptic patients may be related to the geographic characteristics as the mentioned study was carried out in Al-kharga District (New Valley), at the southern part of Egypt, where the majority live in rural areas with a density of 0.58/km 2 , while the majority of our subjects came from Giza, the third-largest city in Egypt and the world's seventh largest suburb, with a density of 2.300/km 2 , and the highest number of traffic accidents as reported by The Central Agency for Public Mobilization and Statistics [15].…”
Section: Etiological Causes Of Symptomatic Epilepsysupporting
confidence: 51%
“…Our results agree with previous reports indicating that head injuries [14] are the most common underlying etiological cause of chronic epilepsy, with males being at a greater exposure risk. When comparing our results with another Egyptian study, led by Farghaly and his colleagues [35], they found that cerebrovascular stroke, rather than trauma, was the most common cause of symptomatic epilepsy among adults and the elderly while perinatal insults were the most common among children (< 18 years). This difference regarding adult epileptic patients may be related to the geographic characteristics as the mentioned study was carried out in Al-kharga District (New Valley), at the southern part of Egypt, where the majority live in rural areas with a density of 0.58/km 2 , while the majority of our subjects came from Giza, the third-largest city in Egypt and the world's seventh largest suburb, with a density of 2.300/km 2 , and the highest number of traffic accidents as reported by The Central Agency for Public Mobilization and Statistics [15].…”
Section: Etiological Causes Of Symptomatic Epilepsysupporting
confidence: 51%
“…For example, the prevalence of early-onset cerebellar ataxia with retained tendon reflexes was lower in northwestern Italy (0.97/100,000 children) 7 compared with the Al-Kharga District in Egypt (3.92/ 100,000 children). 12 Ataxias attributable to environmental causes also varied by region. TAN 8,10 and ataxia as a complication of malaria [29][30][31] were only reported from Africa.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, few studies separate the prevalence of ataxia in children vs adults. [4][5][6][7][8][9][10][11][12] Given the multitude of ataxia-causing conditions and recognizing that each can be quite rare, the overall prevalence of childhood ataxia is likely underestimated. Yet overall prevalence data are needed to accurately assess the impact and societal cost of childhood ataxia.…”
mentioning
confidence: 99%
“…Video monitoring EEG of compliant uncontrolled patients demonstrated that 78.1% patients (n = 50 / 64) had definite epilepsy, while 21.9% (n = 14 / 64) had psychogenic non-epileptic seizures (PNES). A logistic regression analysis revealed that status epilepticus, focal seizures, and mixed seizure types were risk factors for intractability [36]. Uncontrolled epilepsy leads to more stigmatization upon patient with epilepsy.…”
Section: Uncontrolled Epilepsymentioning
confidence: 98%